Locked down through virtual disconnect: Navigating life by staying on/off the health QR code during COVID-19 in China. (December 2021) - Tai, Zixue; Yu, Xiao; He, Bai
During the COVID-19 pandemic, China has implemented the most stringent lockdown measures across major cities during moments of heightened risk of infection. This mechanism is aided by the mandated Health QR Code to surveil and contain spread of the virus. This research scrutinizes the varying degrees and forms of disconnect in the context of the Health Code mandate. Informed by extensive focus group interviews of diverse resident groups, supplemented with thematic analysis of 136 newspaper news stories covering the enforcement of the Health Code, the research results offer insight over the multiplicity of voluntary and involuntary disconnective practices at both the individual/internal and societal/external level. These findings are contextualized for their theoretical relevance towards the overall line of inquiry into information technology non-use, and the pragmatic implications of the Health Code are discussed for contact tracing app design and utility in general.